The Effect of Clinical Supervision and Work Motivation on Teacher Performance - Kurniatie, Amellia; Fitria, Happy; Fitriani, Yessi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study was aimed at examining the clinical supervision and work motivation towards teacher performance. This study was carried out in SMA Negeri 1 Banyuasin III, Banyuasin Regency, South Sumatra Province, and included three schools: SMA Negeri 1 Banyuasin III, SMA Negeri 2 Banyuasin III, and SMA Negeri 3 Banyuasin III. The sample size is 95 respondents. The questionnaire, observation and documentation were used as instruments. Data analysis is done in phases to guarantee that the methods are followed correctly and that the study outcomes can be scientifically validated. The results showed that clinician supervision and teacher work motivation have an influence on the performance of public high school teachers in Banyuasin III sub-district, either partially or jointly. This article provides insight to have clinical supervision and work motivation where the school will have good teacher performance.